A voyage planning tool for Arctic transit of cargo ships - Li, Zhiyuan; Ringsberg, Jonas; Rita, Francisco (Volume 8: Polar and Arctic Sciences and Technology; Petroleum Technology, 2019)
The paper presents a decision-support tool for maritime operations in Arctic seas. This tool targets at improving the safety and fuel efficiency of existing and future cargo vessels that are designed to operate in Arctic and in open water conditions. It is achieved by smart voyage planning using meteorological, oceanographic and ice forecasting.A single-objective optimization for minimizing the fuel consumption in various scenarios of Arctic transits is established, with the transit time and the safety as the two major constraints. The tool is implemented in an in-house Matlab code, which is based on Dijkstra’s algorithm, a grid-based approach that aims at finding the most cost-efficient path connecting any chosen nodes in a given grid. Results from case studies along the Northern Sea Route indicate that the tool generates appropriate routes in ice-infested Arctic waters. The fuel consumption accounting for ice-induced extra resistance is optimized and the risk of collision with icebergs has been considered.